2021
DOI: 10.4142/jvs.2021.22.e68
|View full text |Cite
|
Sign up to set email alerts
|

Colistin resistance and plasmid-mediatedmcrgenes inEscherichia coliandSalmonellaisolated from pigs, pig carcass and pork in Thailand, Lao PDR and Cambodia border provinces

Abstract: Background Colistin and carbapenem-resistant bacteria have emerged and become a serious public health concern, but their epidemiological data is still limited. Objectives This study examined colistin and carbapenem resistance in Escherichia coli and Salmonella from pigs, pig carcasses, and pork in Thailand, Lao PDR, and Cambodia border provinces. Methods The phenotypic and genotypic resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
6
20
1
Order By: Relevance
“…Regarding mobile colistin-resistance genes, few isolates scored positive (5.93%) for one or more genes. This finding is in agreement with other studies reporting a percentage of mcr -positive Salmonella strains ranging between 0.6% and 3.3% [ 15 , 17 , 18 , 19 , 29 ]. The slightly higher positivity detected in our survey may be related to the extended set of investigated genes.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Regarding mobile colistin-resistance genes, few isolates scored positive (5.93%) for one or more genes. This finding is in agreement with other studies reporting a percentage of mcr -positive Salmonella strains ranging between 0.6% and 3.3% [ 15 , 17 , 18 , 19 , 29 ]. The slightly higher positivity detected in our survey may be related to the extended set of investigated genes.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the percentage of colistin-resistant strains was 17.79%, which is slightly higher than the data reported in recent literature. Recent surveys registered percentages of colistin-resistant Salmonella strains ranging between 1% and 12% [ 15 , 17 , 18 , 29 , 30 ]. These differences may be due to many factors: source, geographic area, and serotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacteria carrying mcr gene have been found in humans and animals in many countries. Recently, it has been demonstrated that E. coli strains carrying mcr-1 and mcr-3 genes were found not only in pig feces, but also from contaminated pig carcasses and pork 30 , 31 . This indicates a high risk of spreading bacteria-harboring mcr genes to humans and other environments.…”
Section: Discussionmentioning
confidence: 99%